Development of a highly sensitive chemiluminescence immunoassay for quantification of aggrecanase-generated ARGS aggrecan fragments in serum. Issue 2 (June 2021) - He, Yi; Jensen, Kamilla E.; Siebuhr, Anne Sofie; Karsdal, Morten A.; Larkin, Jonathan; Bay-Jensen, Anne C.
Abstract: Objective: Cartilage degradation is a hallmark of osteoarthritis (OA). Aggrecan, a major proteoglycan of articular cartilage extracellular matrix (ECM), is degraded by ADAMTS-5 resulting in the release of ARGS-G2 fragments to synovial fluid and circulation. The aim was to quantify ARGS-G2 in the serum of OA patients using the huARGS immunoassay. Methods: The immunoassay was produced under GMP conditions and the technical performance was assessed. The biological relevance of the immunoassay was assessed in the conditioned media from a bovine full-depth cartilage explant (BEX) model. The diurnal and inter-day variations of ARGS levels were evaluated in OA patients' serum. Post-hoc analysis of huARGS was conducted in a sub-cohort of a phase III OA trial testing the safety and efficacy of oral salmon calcitonin. Results: Technical performance : huARGS demonstrated good technical performance. Biological relevance : ARGS release was induced by inflamatory facotrs stimulation compared to the vehicle group, reaching a peak at day 3 and gradually decreasing to base level at day 12. The ARGS release was suppressed by the addition of the ADAMTS-4/-5 activation inhibitor. Biological variation : No significant diurnal or inter-day effect was found. Phase III clinical trial: The participants in the lowest group (Q1) of baseline huARGS levels were more likely to progress radiographically than the highest group (Q4): OR 3.38[0.81-14.02]. Conclusions: The huARGS shows good technical performance and low biological variation. It has the potential to aid drug development in various stages, both as a PD biomarker and identifying progressors who might be likely to respond to an OA drug.